Presentation of acute pulmonary edema in severe pre-eclamptic pregnant women: a case report - Chaudhary, Karishma; Tyagi, Mamta; Gupta, Smriti; Gupta, Manvi; Verma, Yamini; Yadav, Kanishka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Pulmonary edema refers to an excessive accumulation of fluid in the pulmonary interstitial and alveolar spaces. It may occur in low risk pregnancies but one very important predisposing factor is association with pre-eclampsia. Acute pulmonary edema during pregnancy is very rare and occurs in 0.08% pregnancies. About 3% of severe pre-eclamptic patients develop acute pulmonary edema. Several risk factors have been identified: preeclampsia or eclampsia, use of tocolytic therapy, severe infection, cardiac disease, iatrogenic fluid overload, and multiple gestations. This case examines one such presentation and reviews some of the diagnostic possibilities.